Oxidative allylic rearrangement of cycloalkenols: Formal total synthesis of enantiomerically pure trisporic acid B - Dubberke, Silke; Abbas, Muhammad; Westermann, Bernhard (Beilstein Journal of Organic Chemistry, 2011)
Enantiomerically highly enriched unsaturated β-ketoesters bearing a quaternary stereocenter can be utilized as building blocks for the synthesis of natural occurring terpenes, i. a., trisporic acid and its derivatives. An advanced building block has been synthesized in a short reaction sequence, which involves an oxidative allylic rearrangement initiated by pyridinium dichromate (PDC) as the key step.
Keywords: enzymatic resolution; natural products; oxidative rearrangement; pig liver esterase (PLE); trisporic acid B